FC/PV Fed SAF with Fuzzy Logic Control for Power Quality Enhancement - R. Balamurugan; R. Nithya (Institute of Advanced Engineering and Science, 2015)
In this paper, a Fuel cell (FC) / Photovoltaic cell (PV)/ Battery operated three phase Shunt Active power Filter (SAF) is proposed for improving the power quality at the utility side. Fuzzy based instantaneous p-q theory control is proposed for SAF. This SAF consists of Voltage Source PWM Converter (VSC) and a DC link capacitor supplied by a FC/PV/Battery. The filter provides harmonic mitigation with reactive power compensation and neutral compensation for loads at the Point of Common Coupling (PCC). A Single switch boost DC-DC converter connects the FC/PV/Battery with the VSC to maintain the load. The performance of the proposed SAF is tested in MATLAB / SIMULINK environment with Fuzzy logic controller (FLC). The controller maintains the DC link voltage based on the current reference generated by the p-q theory. The Hysteresis PWM current controller is employed to generate the gating pulses to the switches in VSC. The simulation results of the proposed SAF validate the effectiveness of FLC in power quality enhancement.